In vivo magnetic particle imaging: angiography of inferior vena cava and aorta in rats using newly developed multicore particles - Mohtashamdolatshahi, Azadeh; Kratz, Harald; Kosch, Olaf; Hauptmann, Ralf; Stolzenburg, Nicola; Wiekhorst, Frank; Sack, Ingolf; Hamm, Bernd; Taupitz, Matthias; Schnorr, Joerg (Scientific Reports, 2020)
Magnetic Particle Imaging (MPI) is a new imaging modality, which maps the distribution of magnetic nanoparticles (MNP) in 3D with high temporal resolution. It thus may be suited for cardiovascular imaging. Its sensitivity and spatial resolution critically depend on the magnetic properties of MNP. Therefore, we used novel multicore nanoparticles (MCP 3) for in-vivo MPI in rats and analyzed dose requirements, sensitivity and detail resolution. 8 rats were examined using a preclinical MPI scanner (Bruker Biospin GmbH, Germany) equipped with a separate receive coil. MCP 3 and Resovist were administered intravenously (i.v.) into the rats’ tail veins at doses of 0.1, 0.05 and 0.025 mmol Fe/kg followed by serial MPI acquisition with a temporal resolution of 46 volumes per second. Based on a qualitative visual scoring system MCP 3–MPI images showed a significantly (P ≤ 0.05) higher image quality than Resovist-MPI images. Morphological features such as vessel lumen diameters (DL) of the inferior vena cava (IVC) and abdominal aorta (AA) could be assessed along a 2-cm segment in mesenteric area only after administration of MCP 3 at dosages of 0.1, 0.05 mmol Fe/kg. The mean DL ± SD estimated was 2.7 ± 0.6 mm for IVC and 2.4 ± 0.7 mm for AA. Evaluation of DL of the IVC and AA was not possible in Resovist-MPI images. Our results show, that MCP 3 provide better image quality at a lower dosage than Resovist. MCP 3-MPI with a clinically acceptable dose of 0.05 mmol Fe/kg increased the visibility of vessel lumens compared to Resovist-based MPI towards possible detection of vascular abnormalities such as stenosis or aneurysms, in vivo.
CRIS-Team Scopus Importer:2022-08-03